2012
DOI: 10.1116/1.3699042
|View full text |Cite
|
Sign up to set email alerts
|

Large area single photon detectors based on parallel configuration NbN nanowires

Abstract: The authors present superconducting single photon detectors (SSPDs) based on parallel nanostrips with an area up to 40 × 40 μm2. The SSPDs presented here are based on 100 nm wide ultrathin NbN nanostrips with a filling factor of 40%. The devices are fabricated by extending the standard electron beam lithography (EBL) patterning process to those densely structured large areas. By a thorough characterization it is shown that the electrical properties of the parallel SSPDs are comparable with those of smaller dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In addition, the fabrication difficulty increases exponentially as the detection area increases. Therefore the maximum detection area reported thus far is only 40 Â 40 m 2 [20] for single nanowire, which is smaller than the core diameter (50 m) of standard multi-mode fibers. Thus, no multi-mode fiber coupled SNSPD with single nanowire has been reported previously.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…In addition, the fabrication difficulty increases exponentially as the detection area increases. Therefore the maximum detection area reported thus far is only 40 Â 40 m 2 [20] for single nanowire, which is smaller than the core diameter (50 m) of standard multi-mode fibers. Thus, no multi-mode fiber coupled SNSPD with single nanowire has been reported previously.…”
Section: Introductionmentioning
confidence: 83%
“…Many attempts [18]- [20] tried to increase the detection area for developing multi-mode fibercoupled SNSPDs. A large active area benefits optical coupling but produces high kinetic inductance, which inevitably degrades the repetition rate of SNSPDs.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the absorption at 850 nm, a specific substrate with a one-dimensional (1-D) photonic crystal (PC) comprising dielectric films are used. The sensitive area diameter is 50 m, which to the best of our knowledge, has the largest sensitive area for a single pixel SNSPD [20][21][22][23]. By optimizing the linewidth and the spacing, the best device showed a maximal DE of 82% and DE of 78% at DCR of 100 Hz, which have prospective applications in free space satellite-ground quantum communication.…”
Section: Introductionmentioning
confidence: 95%
“…Several research groups have reported SNSPDs with a large detection area [15][16][17]. However, fabricating an SNSPD with a large detection area increases the kinetic inductance [18], which determines the repetition rate of the SNSPD, and increases the difficulty encountered during microfabrication.…”
Section: Introductionmentioning
confidence: 98%